Estrategias para mejorar la atención al cliente en la Clínica Veterinaria Faytong de la ciudad de Babahoyo, período 2023 - 2024. - Estupiñán Figueroa, Isis Yannamile (2025)
This research was carried out at the Faytong Veterinary Clinic in the city of Babahoyo, which aims to analyze customer service practices at the Faytong Veterinary Clinic in the city of Babahoyo during the period 2023-2024. On the other hand, this research was framed under the research line "Financial, administrative, tax, audit and control management" and the subline "Marketing and commercialization", which were essential to address the problems. On the other hand, this study will adopt a quantitative approach, seeking to obtain measurable data on the perception of customers regarding the care at the Faytong Veterinary Clinic. It will be descriptive, identifying the problems in the service, and explanatory, exploring the underlying causes that affect the quality of care. Surveys, direct observation and interviews will be used to analyze waiting times, communication, staff training and other factors that impact customer satisfaction. This research is important in offering relevant conclusions and recommendations.